A robust array geometry inversion method for a deep-towed multichannel seismic system with a complex seafloor - Li, Jing; Pei, Yanliang; Liu, Chenguang; Zhang, Liancheng; Luo, Xiaohu; Liu, Kai; Li, Weilu (Frontiers in Marine Science, 2023)
Given the unparalleled advantages in resolution and signal-to-noise ratio, deep-towed multichannel seismic exploration technology has better applicability and more development potential when utilized to invert the geoacoustic properties of deep-sea sediment. Due to the higher requirement for the source-receiver positioning accuracy in ultrahigh resolution seismic detection technology, the accurate geometric inversion results of the receiving array are crucial for fine submarine sediment imaging and physical property parameter inversion based on deep-towed multichannel seismic data. In this paper, we present an array geometry inversion method suitable for complex seafloors to address the challenge of precise source-receiver positioning with deep-towed multichannel seismic systems. Our method does not rely on an initial model, and the objective function of the deep-towed seismic array geometry inversion is built using the shortest path algorithm according to the traveltimes of direct waves and seafloor reflections. Moreover, the particle swarm optimization algorithm is used to achieve high-precision inversion of the source-receiver position. The numerical analyses and field data application results verify the effectiveness of the method proposed in this paper, especially its applicability in scenarios with dramatic changes in seabed topography. Moreover, influencing factor and uncertainty analyses are used to evaluate the dependence of the accuracy of the proposed inversion method on seismic traveltime, seawater velocity and seabed morphology errors. The results provide insights for the accuracy and reliability of the proposed geometric shape inversion method for deep-towed seismic arrays in practical applications to meet the requirements of near-bottom acoustic detection for fine imaging of deep-sea seabed strata and precise inversion of geoacoustic parameters.